PANDANGAN MAHASISWA DALAM PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA KULIAH DOKUMENTASI KEBIDANANMENGGUNAKAN CLASSPOINT - Sigit Setiyanto (LPPM Unbaja, 2023)
Interactive Learning is a learning method or technique that can be applied with a two-way communication system which is characterized by the interaction between lecturers and students, students and students and with learning resources in supporting the achievement of learning objectives. Classpoint is an interactive learning application tool from the company inknoe which can be integrated with the Microsoft Office PowerPoint presentation application and provides a number of features to create interesting learning materials so as to increase student engagement with the subject matter. This study aims to determine student perceptions of the use of Classpoint interactive learning media in lecture activities. The approach method used in this research is a descriptive quantitative approach using a questionnaire. A total of 34 semester 3 students in the undergraduate midwifery study program, the faculty of health sciences at 'Aisyiyah University, Surakarta who took the Religious Education course were given a questionnaire containing 16 statement items representing aspects of motivation, usability, and cognitive and psychomotor aspects. The collected student data is presented using the percentage of perception questionnaire score criteria. The results showed that students gave a positive response to the Classpoint interactive learning media with the criteria of strongly agreeing or a response percentage range of 86.40% to 94.67%. The positive response given to Classpoint media is due to several interesting features that support Classpoint's function as an interactive learning medium. The implication of this research is that Classpoint interactive media can be used as a reference for learning media in class, specifically in increasing student motivation and activeness in learning.